Innovative Nanoparticles Enhance N-Palmitoylethanolamide Intraocular Delivery - Puglia, Carmelo; Blasi, Paolo; Ostacolo, Carmine; Sommella, Eduardo; Bucolo, Claudio; Platania, Chiara B. M.; Romano, Giovanni L.; Geraci, Federica; Drago, Filippo; Santonocito, Debora; Albertini, Barbara; Campiglia, Pietro; et al. (Frontiers in Pharmacology, 2018)
Nanostructured lipid carriers (NLC) loaded with palmitoylethanolamide (PEA) were formulated with the aim to enhance ocular bioavailability of PEA, particularly to the back of the eye. Technological characterization (e.g. size, charge) of NLC loaded with PEA formulation (PEA-NLC) was performed, and NLC morphology was characterized by electron microscopy. Ocular pharmacokinetic study, after topical administration of the formulation, was carried out in rabbit eye. Ultra-high performance liquid chromatography tandem mass spectrometry analysis was carried out to detect PEA levels in ocular tissues. Finally, the ocular tolerability of PEA-NLC formulation was assessed in rabbit eye. The novel formulation significantly increased PEA levels in ocular tissues compared to PEA suspension. Vitreous and retinal levels of PEA were significantly higher in the group treated with PEA-NLC formulation versus PEA suspension (vitreous Cmax 5919 ± 541 pmol/g PEA-NLC 138 ± 30 pmol/g PEA suspension, respectively; retina Cmax 315 ± 70 pmol/g PEA-NLC, n.d. PEA suspension). The PEA-NLC formulation was characterized by high stability and robust ocular bioavailability. Therefore, this innovative formulation may be useful in clinical practice to manage retinal diseases.